Crisis Resilience of European Welfare States: The Role of Multiple Layers of Protection - Werner Eichhorst; Annabelle Krause-Pilatus; Mathias Dolls; Max Lay (Institute of Labor Economics (IZA), 2024)
This paper studies the crisis resilience of European welfare states. We analyse the capacity of social policy arrangements to contain poverty and inequality and avoid exclusion before, during and after periods of economic shocks. To achieve this goal, the paper takes a broad perspective to include different layers of protective arrangements, notably upstream systems such as unemployment insurance (UI), job retention and employment protection that are complemented by minimum income support (MIS) schemes. Together, these multiple layers play a crucial role in providing income and job protection in situations of crisis. In that respect we also distinguish systematically between regular/permanent policies (automatic stabilisers) and discretionary, typically temporary crisis response measures. We use a mixed-method approach that combines quantitative and qualitative research, such as descriptive and multivariate quantitative analyses and microsimulation methods based on EUROMOD. This is combined with in-depth case studies covering a sample of five countries that represent different welfare state types (Nordic, Continental, Mediterranean, Liberal and Central/East European) so that we can show the complex mechanisms of multi-layered protection at work and how the policies in place have evolved over time in response to crisis episodes, disentangling the role of automatic stabilisers and discretionary elements. Our observation period ranges from the mid-2000s to the early 2020s and allows us to cover both the Great Recession of 2008/09 and its aftermath as well as the Covid-19 pandemic. We find consistent differences in terms of crisis resilience across countries and welfare state types. In general, Nordic and Continental European welfare states with strong upstream systems and minimum income support show better outcomes in core socio-economic outcomes such as poverty and exclusion risks. However, labour market integration shows some dualisms in Continental Europe. The study shows that minimum income support holds particular importance if there are gaps in upstream systems or cases of severe and lasting crises.
Keywords: J65; J68; I38; 330; minimum income support; crisis resilience; unemployment insurance; job retention; welfare states